Impact of Russia-Ukraine Conflict on the stock prices of US oil companies - Ulessi, Matjas (My University, 2025)
This paper explores the impact of the Russia-Ukraine conflict on the stock prices of US oil companies. The study aims to determine the degree of benefit to the US oil industry following the immediate outbreak of the crisis. The study employs a market-adjusted return model to analyze the Average Abnormal Returns (AAR) and Cumulative Abnormal Returns (CAR) of a sample of American oil company stocks. These returns serve as a proxy for market sentiment. The analysis focuses on the event window surrounding the start of the conflict to assess its impact on the market behavior. The background of the conflict is explored, along with its escalation following Russia's annexation of Crimea in 2014. The study also reports the economic sanctions imposed by the US, EU, and other countries on Russia, and Russia's countermeasures. Furthermore, the literature review covers key concepts such as geopolitical crises, market interconnectedness, spillover effects across financial markets and countries, inflationary pressures, and the energy trade landscape. The data collected includes daily stock prices of US oil companies and the S&P500 index, which serves as a benchmark. The study utilizes regression analysis to calculate the statistical significance of AAR and CAR. The empirical findings indicate a statistically significant positive CAR in the window (-3, +3), suggesting positive market sentiment towards the oil sector. This result supports the hypothesis that positive sentiment towards the oil sector counteracts the market shock of the event itself. In conclusion, the thesis provides insights into the effects of the Russia-Ukraine conflict on the US oil sector by analyzing market sentiment through AAR and CAR. The research also identifies and analyzes how expectations of supply disruptions, increased demand for non-Russian oil, and the strategic importance of energy security have influenced market sentiment towards the oil industry. The findings support the hypothesis that there is a significant positive CAR in the window surrounding the start of the Russia-Ukraine conflict.
Keywords: Russia; oil; economic crises; geopolitics; crises; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance